2017
DOI: 10.1159/000451011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Liver Inflammation on Liver Stiffness Measurement in Patients with Autoimmune Hepatitis Evaluation by Combinational Elastography

Abstract: Objective: In order to evaluate the influence of liver inflammation on liver stiffness measurement (LSM) by the simultaneous use of shear wave and strain imaging (combinational elastography), shear wave and strain imaging were compared before and after initial therapy for autoimmune hepatitis (AIH). Methods: Nine AIH patients initially treated with steroid were enrolled. Transient elastography and real-time tissue elastography were performed just before and 1 month after the start of initial steroid treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
1
19
0
3
Order By: Relevance
“…In these participants, treatment decision may rely on clinical data rather than on liver stiffness values. In fact, inflammation was proven to be an important confounding factor of liver stiffness measurements in our study, which negatively impacted the diagnostic performance of 2D SWE, as was shown in previous studies (28,29). In this study, AUCs of 2D SWE were higher in A0-A2 than were those in A3 in participants with advanced fibrosis, and, especially in cirrhosis (P = .001).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In these participants, treatment decision may rely on clinical data rather than on liver stiffness values. In fact, inflammation was proven to be an important confounding factor of liver stiffness measurements in our study, which negatively impacted the diagnostic performance of 2D SWE, as was shown in previous studies (28,29). In this study, AUCs of 2D SWE were higher in A0-A2 than were those in A3 in participants with advanced fibrosis, and, especially in cirrhosis (P = .001).…”
Section: Discussionsupporting
confidence: 66%
“…Second, the centers that participated in our study were all high-level teaching hospitals in different regions of China and a prevalence bias was observed, in which participants were more likely to be in the severe stages of disease. Third, inflammation could impact the diagnostic performances of liver stiffness measurement (28,29). Approximately two-thirds of participants in our study were in the chronic hepatitis group, which indicated that they were more likely to be in severe stages of inflammation.…”
Section: Discussionmentioning
confidence: 76%
“…Strain imaging such as RTE is not affected by inflammation, jaundice, or congestion [1,2,32,33] . In this study, we analyzed only cases without jaundice and congestion to evaluate fibrosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TE has also been applied in the study of autoimmune liver disease, with excellent diagnostic performance (166), though several studies have reported that acute inflammation as a result of autoimmune hepatitis may affect liver stiffness (167,168). TE has also been shown to be an accurate method for staging fibrosis in primary biliary cirrhosis (169-171), primary sclerosing patients (Fig 4).…”
Section: Other Etiologies Of Liver Diseasementioning
confidence: 99%